Plano de Negócios: App Auau Help - MOREIRA, Hellen Jéssica; MONTEIRO, Matheus Armando; NARCIZO, Mirna de Fátima Alves Vieira; NAKAMURA JÚNIOR, Nelson (Em memória) (133, 2021)
O modelo estudado, denominado Au Au Help, foi desenvolvido para ser utilizado como ferramenta de divulgação comercial prática, simples e eficaz a ser empregado como um aplicativo mobile, ou seja, através de um software que desempenha suas funções em smartphones e tabletes. Em conformidade com o método experimental utilizado, realizou-se uma pesquisa bibliográfica acerca dos assuntos que norteiam o funcionamento e aplicabilidade do produto estudado em busca de informações que sirvam de base para definição de cada detalhe na composição do produto, ou seja, itens que irão compor o aplicativo. A partir da pesquisa deu-se o desenvolvimento do aplicativo através de ferramentas técnicas e conhecimento específico da área de tecnologia da informação. E, buscando avaliar sua viabilidade foi desenvolvido e aplicado um questionário com perguntas fechadas que permitiram identificar o interesse, bem como potencial aceitação e uso do aplicativo por parte dos entrevistados. Realizado o questionário, fez-se necessário analisar e qualificar as informações colhidas identificando nelas dados que, em conjunto com o conhecimento adquirido por meio das pesquisas, discriminam no aplicativo a capacidade de causar alterações e/ou melhorias na relação empresa – comércio - cliente do setor pet online. Por meio de abordagem descritiva, realizou-se uma pesquisa qualitativa através de aplicação de um questionário online com perguntas fechadas que buscaram coletar informações a respeito de características do público, como sexo, idade, renda, escolaridade e número de pessoas que moram na mesma casa. Salientando o interesse por animais de estimação e participação no comércio pet, incluíram-se questões voltadas para quantidade e preferência por animais, assiduidade em compras pet e local preferido para compras. Além de informes relacionados ao uso de internet e compras via internet através de smartphones. E, para reconhecimento do interesse público em torno do diferencial do aplicativo foram elencadas perguntas acerca do interesse e frequência com que os entrevistados Ajudam ONGs ou efetuariam compras em prol de uma ação social animal. Ponderando particularidades e experiências dos entrevistados, a abordagem serviu de base e estrutura para viabilidade do projeto.

The studied model, called Au Au Help, was developed to be used as a practical, simple, and effective commercial dissemination tool, intended to be implemented as a mobile application, that is, through software that operates on smartphones and tablets. In accordance with the experimental method used, a literature review was conducted on the topics that guide the operation and applicability of the studied product, seeking information to serve as a basis for defining each detail in the product's composition, that is, the items that will make up the application. Based on the research, the application was developed using technical tools and specific knowledge in the field of information technology. In order to assess its feasibility, a questionnaire with closed-ended questions was developed and applied, allowing the identification of interest, as well as the potential acceptance and use of the application by the respondents. The model studied, called Au Au Help, was developed to be used as a practical, simple, and effective commercial dissemination tool, intended to be employed as a mobile application, that is, through software that performs its functions on smartphones and tablets. In accordance with the experimental method used, a literature review was conducted on the topics that guide the operation and applicability of the product studied in search of information that serves as a basis for defining every detail in the product composition, that is, the items that will make up the application. Based on the research, the application was developed using technical tools and specific knowledge in the field of information technology. And, seeking to assess its feasibility, a questionnaire with closed-ended questions was developed and applied, allowing the identification of interest, as well as the potential acceptance and use of the app by the respondents. Once the questionnaire was conducted, it became necessary to analyze and qualify the collected information, identifying data that, together with the knowledge acquired through research, highlight in the app the ability to cause changes and/or improvements in the company–commerce–client relationship in the online pet sector. Through a descriptive approach, a qualitative study was carried out by applying an online questionnaire with closed-ended questions aimed at collecting information about the audience's characteristics, such as gender, age, income, education level, and the number of people living in the same household. Highlighting interest in pets and participation in the pet trade, questions were included regarding the number and preference for animals, frequency of pet-related purchases, and preferred place for shopping. In addition to information related to internet use and online shopping via smartphones. And, to recognize public interest in the app's differentiating factor, questions were listed regarding the interest and frequency with which respondents help NGOs or make purchases in support of an animal social cause. Considering the particularities and experiences of the respondents, the approach served as the basis and structure for the project's feasibility.
Business plan: App Auau Help
Keywords: Negócios - Plano; Inovação; Marketing; Empreendedorismo; Investimentos; Gestão e Negócios